Unenhanced Time-of-Flight MR Angiography versus Gadolinium-Enhanced Time-of-Flight MR Angiography in the Follow-Up of Coil-Embolized Aneurysms - Behme, D.; Malinova, V.; Kallenberg, K.; Knauth, M.; Mohr, A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background and Purpose Coil embolization of ruptured and unruptured aneurysms has emerged as a widely accepted alternative to clipping. Unfortunately, coil-embolized aneurysms need a long-term imaging follow-up to confirm the stability of the occlusion status. We investigated whether contrast-enhanced time-of-flight (ToF) magnetic resonance angiography (MRA) (gadolinium [Gd]-ToF) provides any diagnostic benefit over conventional ToF MRA (nonenhanced [NE]-ToF) in this context.Material and Methods From October 2013 to January 2015, all patients who were regularly scheduled for their follow-up after coil embolization were examined with Gd-ToF and NE-ToF angiography. The general visibility of the occlusion result was compared between the two MRAs as well as with the last digital subtraction angiography (DSA) available. Subgroups of interest (follow-up after stent-assisted coil embolization, cases with already known aneurysm remnants) were also analyzed.Results A total of 70 patients (44 female) harboring 74 treated aneurysms were examined. The reproducibility of the DSA result in terms of therapeutic relevance was 100%. In 10 of 74 cases (14%), the aneurysm status was more difficult to judge in the NE-ToF images (p = 0.02), and the visualization of small vessels was significantly better in the Gd-ToF (p = 0.003). NE-ToF did not fail to show any aneurysm remnants but were more difficult to depict in 35% of the cases (p = 0.09). Regarding the aneurysms that were coiled with stent assistance, there was no significant difference in terms of the visualization (p = 0.1).Conclusion Gd-ToF angiography is in general not superior to NE- ToF for the follow-up of coil-embolized aneurysms.
Keywords: aneurysm; coil embolization; time of flight